Comparison of organic electrolytes at various temperatures for 2.8 V–Li-ion hybrid supercapacitors. (20th March 2020) - Shim, H.; Budak, Ö.; Haug, V.; Widmaier, M.; Presser, V.
Abstract: We explore different electrolytes containing lithium perchlorate (LiClO4 ) and lithium bis(trifluoromethylsulfonyl)imide (LiTFSI) salts in various solvents at different temperatures to associate the electrochemical stability of lithium titanium oxide (LTO)/lithium manganese oxide (LMO)-activated carbon (AC) composite Li-ion hybrid supercapacitors. By varying the solvents and operation temperature, we were able to detect a correlation between the electrochemical performance and the conductivity of each electrolyte. To test the electrochemical stability and longevity of the electrolytes in such a system, full-cells were analyzed via a voltage floating for 10 h at charged state (2.8 V) of the full-cell. Energy and power performance were the highest for acetonitrile (ACN) containing electrolytes due to their high lithium-ion conductivity. Additionally, the longevity of LiClO4 in 3-methoxypropionitrile (3-MPN) was superior to all tested electrolytes at ambient temperature with 97% capacity retention and energy efficiency of about 86% after 500 h of voltage floating. LiClO4 in a mixture of ACN and ethylene carbonate (EC) was the most stable electrolyte at high temperatures with 70% capacity retention after 500 h voltage floating at 60°C and 50% capacity retention after 250 h voltage floating. The longevity of LiTFSI in ACN and LiClO4 in 3-MPN electrolyte demonstrated a capacity retention of 97% and 92% after 500 h voltage floating, respectively, at low temperature (−10 °C). Graphical abstract: Image 1